Diaspora, Neighborhood, Empire: Sir Gawain and the Green Knight. (2nd July 2020) - Coley, David K.
ABSTRACT: Beginning with a consideration of double identity that the Gawain -poet develops for Aeneas and his band of Trojan exiles — on the one hand, a scattered and traumatized people marked by the loss of their ancestral homeland; on the other hand, a colonizing force establishing dominance throughout Europe — this article examines the mingled diasporic and colonial formations of Sir Gawain and the Green Knight ( SGGK ) through the lens of Avtar Brah's concept of "diaspora space, " as well through overlapping ideals of the neighborhood and neighboring. I propose that the Gawain -poet generates in his work a fictive diaspora space defined by hybridity and mutual benefit, one that insists on the productive presence and interpenetration of indigenous, diasporic, and colonial groups within the region of "Norþe Walez." This sunny vision of the Anglo-Welsh borderlands, however, is strikingly at odds with the realities of the Anglo-Welsh relationship in the fourteenth century, one that may indeed have been defined by hybridity but that was hardly mutually beneficial, at least not where the Welsh were concerned. I argue here that SGGK not only willfully misrepresents the Anglo-Welsh relationship in its fictive diaspora space but that, in so doing, it tacitly provides literary cover for the English subjugation of the Welsh and implicitly supports England's nascent colonial ambitions.